A longitudinal study of the effects of well-being and perceived control on preparations for old age: moderation effects of contexts - Park, Jeongsoo; Hess, Thomas M.; Fung, Helene H.; Kornadt, Anna; Rothermund, Klaus (European Journal of Ageing, 2022)
Extending research on determinants of preparations for old age across adulthood, we examined the relationship between well-being, perceived control, and preparations for old age over time, along with variation in the strength of these relationships depending on domains of functioning, cultures, and age. We analyzed longitudinal data from the Ageing as Future study assessing changes in well-being, perceived control, and preparations in four different life domains (social relations, finances, work, and health) across a five-year period collected from adults aged from 30 to 85 years in Germany (N = 623), Hong Kong (N = 317), and the USA (N = 315). Positive feelings about one’s current situation predicted greater perceived control five years later, and vice versa. Also, perceived control and preparations were positively associated over time, with only a few exceptions within each domain. For example, high control beliefs were related to subsequent greater preparations and well-being within the domain of social relations and finances, with weak effects of culture. These results suggest that current well-being may promote adaptive behaviors in later life, with the accumulated effects over time. Thus, focusing on how to improve our well-being may promote engagement in preparations for old age. Our results also indicate that these relations in our model vary by contexts, highlighting the importance of variability in age-related processes.
Keywords: Context; Control beliefs; Culture; Preparations for aging; Well-being